Application of Comprehensive Geophysical Prospecting Method in Water Accumulation Exploration of Multilayer Goaf in Integrated Mine - Lei Zhang; Lin Xu; Yong Xiao; NingBo Zhang (Advances in Civil Engineering)
A coal mine in Datong is an integrated mine. At present, there is goaf in the upper and lower part of the mining coal seam. There is a lot of ponding in the goaf, which has great potential safety hazards for production. In order to find out the scope and location of ponding in goaf, the comprehensive geophysical exploration method combining transient electromagnetic method and high-density resistivity method is used to carry out the research. Firstly, the time-base, turn-off time, receiving delay, current, superposition times, and other parameters of the instrument are tested on the surface of known goaf to obtain the best instrument parameters, and the parameters are used to verify the feasibility of the research scheme; then, the transient electromagnetic method is used for large-area exploration on the surface of the mine, the suspected goaf ponding area is found through comprehensive analysis, and the high-density resistivity exploration is arranged in the suspected goaf ponding area. According to the obtained results, the scope and location of the goaf ponding area are accurately located through comprehensive analysis. The results show that there are two goaf ponding areas in the exploration area, which are located above the 8# coal seam currently mined; the range and location of goaf ponding area can be accurately obtained by using the comprehensive geophysical method of high-density electrical method and transient electromagnetic method. This method can provide reference for mine water prevention and control in Datong area and has great practical significance to ensure coal mine safety production.